2013
DOI: 10.3329/cerb.v16i1.17470
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Bed Adsorption Separation Of Xylene Isomers over SiO2/Silicallite-1 Core-Shell Adsorbents

Abstract: Abstract:SiO 2 /Silicalite-1 core-shell material has been demonstrated as potential shape selective adsorbent in gas phase separation of p-xylene from a mixture of p/o-xylene isomers. The core-shell composite comprised of large silica core and thin polycrystalline silicalite-1 shell which was synthesized via a self-assembly of silicalite-1 nanocrystals on core silica surface followed by a secondary seeded growth method. The core materials, SiO 2 used in this study has mesoporosity with an average pore diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Binary breakthrough experiments at 423 K showed a high selectivity of 15 for PX/OX. Further research concluded that PX/OX selectivity arose solely from a molecular sieving effect of the silicalite-1 shell, while the core possessed no selectivity . A ZSM-11/silicalite-2 core–shell molecular sieve with a compact silicalite-2 shell also proved effective for the separation of xylenes…”
Section: Molecular Sievesmentioning
confidence: 99%
“…Binary breakthrough experiments at 423 K showed a high selectivity of 15 for PX/OX. Further research concluded that PX/OX selectivity arose solely from a molecular sieving effect of the silicalite-1 shell, while the core possessed no selectivity . A ZSM-11/silicalite-2 core–shell molecular sieve with a compact silicalite-2 shell also proved effective for the separation of xylenes…”
Section: Molecular Sievesmentioning
confidence: 99%
“…Matching with theoretical expectations, the smaller hydrocarbons were efficiently separated from the large ones by the shape‐selective silicalite‐1 shell (Figure d). Following this, core@shell and hollow zeolites were successfully used for several gas or liquid phase adsorptive separation processes, as listed in Tables . The importance of the film quality and thickness, i.e., fewer defects, pinholes, and cracks, as well as the orientation of the crystals to determine the separation performances of zeolitic membranes was also discussed extensively .…”
Section: Applications Of Core@shell Hollow and Yolk–shell Zeolitic mentioning
confidence: 99%
“…The desirable final products, non-aggregated core@shell microspheres, should meet a set of quality criteria including the preserved core mesoporosity during the shell formation process, complete shell coverage, pore network connectivity between constituents of the composite, and the absence of free zeolite crystals in the bulk. Although there are few examples of core@zeolite that can be produced by using a onepot hydrothermal crystallization process [22][23][24][25][26] , the synthesis of a great number of zeolitic core@shell materials is only viable through a multi-step synthesis route 3,4,9,11,12,15,21,[27][28][29][30][31][32][33] . The multistep synthesis route usually involves preliminary adsorption of zeolite nanocrystals onto large core particles followed by growing these nanocrystals in an appropriate synthesis gel mixture 34,35 (Scheme 1).…”
Section: Page 3 Of 33 Crystengcommmentioning
confidence: 99%
“…In particular, high surface area, high pore volume mesoporous silica spheres with the ability of hosting various functional groups (e.g., metals, metal oxides, etc.) when finely covered with a zeolitic shell may hold considerable promise in a variety of applications [11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation